Managerial Job Assignment and Imperfect Competition in Asymmetric - Volker Grossmann (Institute for the Study of Labor (IZA), 2003)
This paper develops a model with multiple market locations in which the quality of intangible assets of firms, provided by management, determines the firms? performance. Despite an exante symmetry of potential entrants, the equilibrium assignment of heterogeneous managerial skills to firms tends to be asymmetric. This sorting outcome determines both the goods market structure at single locations and the size distribution of firms. Results are consistent with a number of observed patterns regarding the size distribution of firms and establishments, and the relation of firm size to profitability, productivity, managerial skills and manager remuneration.
Keywords: D40; J31; L16; 330; asymmetric equilibrium; firm size; intangible assets; managerial jobassignment; Führungskräfte; Qualifikation; Intangibles Gut; Markteintritt; Unvollkommener Wettbewerb; Industrieökonomik; Gleichgewicht; Theorie